Cross-Talk Studies between FCC-hh Experimental Interaction Regions - Abelleira Fernandez, J; Seryi, A; Appleby, R; Rafique, H; Besana, M (JACoW, 2017)
Debris from 50 TeV proton-proton collisions at the main interaction point in the FCC-hh may contribute to the background in the subsequent detector. This cross-talk is of possible concern for the FCC-hh due to the high luminosity and energy of the collider. DPMJET-III is used as a collision debris generator in order to assess the muon cross-talk contribution. An analytical calculation of muon range in rock is performed. This is followed by a full Monte Carlo simulation using FLUKA, where the accelerator tunnel has been modelled. The muon cross talk between the adjacent interaction points is assessed and its implications for FCC-hh design are discussed.